The Effect of Supervision and Control on the Performance of Planning and Budgeting Officials with the Transfer of Command at Kodiklatad - Widiasih, Tri; Sembiring, Ferikawita Magdalena (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Achmad Yani, 2026)
The Indonesian Army is always trying to improve the performance of its personnel, one of which is at the Indonesian Army Education and Training Command, due to a decline in the performance of planning and budget officers of the Indonesian Army Education and Training Command, as seen from the 2024 performance assessment, which is estimated to be influenced by suboptimal supervision and control. The purpose of this study is to analyze the effect of supervision and control on the performance of planning and budget officers of the Indonesian Army Education and Training Command work units. The research method employed is a quantitative approach, with 42 respondents comprising planning and budget officers from the Indonesian Army Education and Training Command's work units. The analysis method utilizes multiple linear regression, while the sampling technique employs random sampling. The results of the study showed that there was a positive and significant influence between supervision on performance, there was a positive and significant influence between control on performance, then the results of this study also showed that there was a positive and significant influence between supervision and control on the performance of planning and budget officers of the Indonesian Army Education and Training Command work units. The increasing supervision and control will also increase the performance of planning and budget officers of the Indonesian Army Education and Training Command's work units.